Moisture power generation fabric as well as preparation method and application thereof
By modifying the conductive and hydrophilic materials on the fabric substrate, constructing a coated area with different asymmetric hygroscopic absorbance and loading gel-state hygroscopic power generation functional materials, the problem of stable power generation of moisture-generating materials under changing weather conditions is solved, and all-weather sustainable power generation and good wearable performance are achieved.
Patent Information
- Application Number
- CN202410190005.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-02-20
- Publication Date
- 2025-08-22
AI Technical Summary
Existing moisture-generating materials cannot generate electricity stably for a long time under changing weather conditions, and have poor wearable performance. Traditional materials are sensitive to environmental humidity and temperature, and their flexibility and breathability are limited.
The surface of the fabric substrate is used to modify the conductive and hydrophilic reinforcement materials. The coated areas and uncoated areas form asymmetric hygroscopic differences, and the gel-state hygroscopic power generation functional materials are loaded. The charge transfer effect and ion occupation effect are used to improve the proton transmission efficiency, form a stable electric field output, and realize energy conversion by relying on environmental moisture.
It realizes sustainable power generation at any time and place, with good flexibility and breathability, breaking through the limitations of traditional moisture power generation materials in the wearable field, and the power generation performance can be quantitatively controlled by adjusting the composite parameters of power generation.
Smart Images

Figure CN120520073A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of functional materials, and in particular relates to a moisture-generating fabric and a preparation method and application thereof. Background Art
[0002] With the increasing intelligence and miniaturization of electronic devices, wearable electronics are becoming increasingly important in our lives. Currently, commercial wearable electronics are primarily powered by chemical batteries, which lack flexibility, are relatively heavy, and require frequent charging. These drawbacks severely limit their application scenarios. Therefore, developing textile materials that can generate sustainable power around the clock could help promote the rapid development of wearable electronics.
[0003] As an abundant renewable resource on Earth, water is not only essential for life but also the largest energy carrier. Water vapor, in particular, is present in all areas of human life and easily accessible at any time, yet the abundant energy it contains is often overlooked. In recent years, wet gas power generation, based on the interaction between hygroscopic materials and water, has become a new hot topic in energy research. Besides ambient humidity, wet gas power generation requires few additional conditions and is therefore considered a very promising green energy conversion method.
[0004] Currently, most reported moisture-generating materials have the following problems: they are often very sensitive to ambient humidity and temperature, and cannot generate electricity stably for long periods of time in ever-changing weather conditions; the water gradient within the material eventually disappears as moisture absorption reaches equilibrium, meaning these moisture-generating materials cannot generate electricity sustainably; and the formation of the internal water gradient in most moisture-generating materials requires the encapsulation of asymmetric electrodes, which often affects flexibility and breathability, thus limiting their wearable applications. Therefore, developing textile materials capable of all-weather sustainable power generation for the moisture-generating link will help promote the rapid development of wearable electronics. Summary of the Invention
[0005] The purpose of this application is to provide a moisture-generating fabric and its preparation method and application, aiming to solve to a certain extent the problem that existing moisture-generating materials cannot generate electricity stably for a long time and have poor wearability.
[0006] To achieve the above application objectives, the technical solutions adopted in this application are as follows:
[0007] In a first aspect, the present application provides a moisture-generating fabric, comprising a fabric base, wherein the surface of the fabric base is modified with a conductive and hydrophilic reinforcing material, wherein the modified surface of the fabric base comprises a coated area and an uncoated area relative to each other, wherein the coated area and the uncoated area form an asymmetric hygroscopic difference that drives proton transport; wherein the coated area is loaded with a gel-state hygroscopic power generation functional material, wherein the hygroscopic power generation functional material comprises a hygroscopic base material, a charge transfer material, a proton dissociation material, and an antifreeze material; wherein the hygroscopic power generation functional material improves proton transport efficiency through a charge transfer effect and an ion occupation effect;
[0008] The power generation performance of the wet air power generation fabric is determined by a power generation composite parameter, and the power generation performance of the wet air power generation fabric and the power generation composite parameter show a nonlinear relationship that first increases and then decreases, that is, as the value of the power generation composite parameter increases, the power generation performance of the wet air power generation fabric first increases and then decreases; by controlling and adjusting the power generation composite parameter, the power generation performance of the wet air power generation fabric is quantitatively controlled and adjusted; the power generation composite parameter is the product of the stable power generation time and the sum of the relative humidity and temperature under the same weight, and the quotient of the difference in water evaporation on both sides of the coupling interface.
[0009] The first aspect of the present application provides a moisture-generating fabric. On the one hand, in the coating area of the modified fabric substrate, a gel-state moisture-generating functional material is formed by the synergistic effect of a moisture-absorbing base material, a charge transfer material, a proton dissociation material, and an antifreeze material. The diffusion barrier of protons in the chromatographic mass transfer process is reduced by the charge transfer effect and the ion occupation effect, thereby improving the proton transfer efficiency. The moisture-absorbing power generation functional material with strong hygroscopicity and the flexible fabric with weak hygroscopicity are coupled, and the permanent asymmetric hygroscopicity difference on both sides of the coupling interface is used as a stable driving force for proton transfer, thereby achieving a long-lasting, stable, and sustainable output of electrical performance, effectively solving the problem that traditional moisture-generating materials cannot generate electricity stably for a long time in changing weather conditions. On the other hand, with fabric as the substrate, the fabric has good flexibility and does not require additional packaging of hard electrodes, so it has good flexibility and breathability, effectively breaking through the limitation that traditional moisture-generating materials are difficult to apply in the wearable field. The moisture-generating fabric of the present application is based on the basic principle of moisture-generating power. It utilizes the hygroscopic groups such as hydroxyl, carboxyl, and sulfonic acid groups on the surface of the fabric substrate, especially the surface of the moisture-absorbing power-generating functional material loaded in the coating area, to spontaneously absorb water molecules from the environment and dissociate a large number of protons after contact with water molecules. The water gradient constructed by the coated area and the uncoated area of the fabric substrate can make these positively charged internal protons spontaneously migrate in a directional manner, forming an electric field inside the material, thereby forming a stable external electrical output. In addition, the moisture-generating fabric of the present application does not require additional mechanical energy, temperature difference, light and other conditions. It can achieve energy conversion and electrical output only by relying on the moisture in the environment. Therefore, it can be used as an all-weather power source to power wearable electronic products at any time and any place. In addition, the power generation performance of the moisture-generating fabric of the present application is determined by the power generation composite parameter (i.e., the product of the stable power generation time and the relative humidity and temperature of the environment under the same weight, and the quotient of the difference in water evaporation on both sides of the coupling interface). That is, as the value of the power generation composite parameter increases, the power generation performance of the moisture-generating fabric first increases and then decreases. Therefore, by adjusting the power generation composite parameter, the power generation performance of the moisture-induced all-weather sustainable power generation fabric can be quantitatively controlled and optimized.
[0010] In a second aspect, the present application provides a method for preparing the above-mentioned moisture-generating fabric, comprising the following steps:
[0011] Obtaining a fabric substrate, and modifying the surface of the fabric substrate with a reinforcing material having conductivity and hydrophilicity to obtain a modified fabric substrate;
[0012] Formulating a hygroscopic power generation functional material comprising a hygroscopic base material, a charge transfer material, a proton dissociation material and an antifreeze material;
[0013] The surface of the modified fabric substrate is divided into a coated area and an uncoated area relative to each other, and the gel-state hygroscopic power generation functional material is loaded on the coated area to obtain a moisture power generation fabric.
[0014] The present invention discloses a method for preparing a moisture-generating fabric using a fabric as a substrate, exhibiting excellent flexibility and breathability, and suitable for direct wearable applications. The surface of the fabric substrate is modified with a conductive and hydrophilic reinforcing material to improve the hydrophilicity and conductivity of the fabric substrate. The modified surface of the fabric substrate is divided into opposing coated and uncoated areas. The coated areas are then loaded with a hygroscopic, power-generating functional material comprising a hygroscopic base material, a charge transfer material, a proton dissociation material, and an antifreeze material, to produce a moisture-generating fabric. The preparation process is simple and suitable for large-scale commercial production and application. The moisture-generating fabric described in this application requires no additional mechanical energy, temperature differences, or light; it relies solely on ambient moisture to achieve energy conversion and electrical output. The coated areas of the fabric substrate contain a large number of hygroscopic groups that spontaneously absorb water molecules from the environment and, upon contact with the water molecules, dissociate a large number of protons. This creates a water gradient between the coated and uncoated areas, allowing these positively charged internal protons to spontaneously migrate in a directional manner, forming an electric field within the material and thus generating a stable external electrical output.
[0015] In a third aspect, the present application provides an application of a moisture-generating fabric, wherein the moisture-generating fabric or the moisture-generating fabric prepared by the above method is applied to a moisture-induced power generation device.
[0016] The moisture-generating textiles described in this application require no additional mechanical energy, temperature differences, or light, relying solely on ambient moisture to achieve energy conversion and electrical output. Consequently, these textiles can be incorporated into moisture-induced power generation devices, serving as an all-weather power source for wearable electronics and other devices at any time and in any location. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the following briefly introduces the drawings required for use in the embodiments or descriptions of the prior art. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without any creative work.
[0018] Figure 1 This is a schematic structural diagram of the moisture power generation fabric provided in an embodiment of the present application;
[0019] Figure 2 1 is a schematic flow chart of a method for preparing a moisture-generating fabric provided in an embodiment of the present application;
[0020] Figure 3 This is a schematic structural diagram of the moisture power generation fabric provided in Example 1 of the present application connected to an electrical collector;
[0021] Figure 4 This is a schematic structural diagram of the moisture power generation fabric provided in Example 1 of the present application connected to an electrical device;
[0022] Figure 5 This is a graph showing the open circuit voltage and short circuit current data recorded by an electrometer of the moisture power generation fabric provided in Example 1 of the present application;
[0023] Figure 6 This is a graph showing the rate of change of the electrical properties of the moisture-generating fabric provided in Example 1 of the present application as the composite parameters of power generation are adjusted;
[0024] Figure 7 This is a schematic structural diagram of the moisture power generation fabric provided in Example 2 of the present application connected to an electrical collector;
[0025] Figure 8 This is a schematic diagram of the structure of the moisture power generation fabric provided in Example 2 of the present application connected to an electrical device;
[0026] Figure 9 This is a graph showing the open circuit voltage and short circuit current data recorded by an electrometer of the moisture power generation fabric provided in Example 2 of the present application;
[0027] Figure 10 This is a graph showing the rate of change of the electrical properties of the moisture-generating fabric as the composite power generation parameters are adjusted, as provided in Example 2 of the present application;
[0028] Figure 11 This is a schematic structural diagram of the moisture power generation fabric provided in Example 3 of the present application connected to the electricity collector;
[0029] Figure 12 This is a schematic structural diagram of the moisture power generation fabric provided in Example 3 of the present application connected to an electrical device;
[0030] Figure 13 This is a graph of open circuit voltage and short circuit current data recorded by an electrometer for the moisture power generation fabric provided in Example 3 of the present application;
[0031] Figure 14 This is a graph showing the rate of change of the electrical properties of the moisture-generating fabric provided in Example 3 of the present application as the composite parameters of power generation are adjusted.
[0032] The reference numerals in the figures are: 1—uncoated area 2—coated area. DETAILED DESCRIPTION
[0033] In order to make the technical problems, technical solutions and beneficial effects to be solved by this application more clearly understood, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain this application and are not intended to limit this application.
[0034] In this application, the term "and / or" describes the relationship between associated objects, indicating that three possible relationships exist. For example, A and / or B can represent: A exists alone, A and B exist simultaneously, and B exists alone. A and B can be singular or plural. The character " / " generally indicates that the associated objects are in an "or" relationship.
[0035] In this application, "at least one" means one or more, and "plurality" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b or c", or "at least one of a, b and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple.
[0036] It should be understood that in the various embodiments of the present application, the size of the serial numbers of the above-mentioned processes does not mean the order of execution. Some or all of the steps can be executed in parallel or sequentially. The execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.
[0037] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments and are not intended to limit the present application. The singular forms "a", "an" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms unless the context clearly indicates otherwise.
[0038] The weights of the relevant components mentioned in the examples of this specification may not only refer to the specific content of each component, but also represent the weight ratio between the components. Therefore, as long as the content of the relevant components in the examples of this specification is proportionally enlarged or reduced according to the examples of this specification, it is within the scope disclosed in the examples of this specification. Specifically, the mass described in the examples of this specification may be μg, mg, g, kg, etc., which are mass units commonly known in the chemical industry.
[0039] The terms "first" and "second" are used solely for descriptive purposes to distinguish objects, such as substances, from one another and should not be understood to indicate or imply relative importance or to implicitly specify the quantity of the technical features being referred to. For example, without departing from the scope of the embodiments of this application, a first XX may also be referred to as a second XX, and similarly, a second XX may also be referred to as a first XX. Thus, features defined as "first" or "second" may explicitly or implicitly include one or more of such features.
[0040] The first aspect of the embodiment of the present application provides a moisture power generation fabric, as shown in the attached Figure 1 As shown, it includes a fabric substrate, the surface of the fabric substrate is modified with a conductive and hydrophilic reinforcing material, the modified surface of the fabric substrate includes a coated area 2 and an uncoated area 1 relative to each other, and the coated area 2 and the uncoated area 1 form an asymmetric hygroscopic difference that drives proton transport; wherein the coated area 2 is loaded with a gel-state hygroscopic power generation functional material, the hygroscopic power generation functional material includes a hygroscopic base material, a charge transfer material, a proton dissociation material and an antifreeze material; the hygroscopic power generation functional material improves the proton transport efficiency through the charge transfer effect and the ion occupation effect;
[0041] The power generation performance of the wet air power generation fabric is determined by the power generation composite parameter, and the power generation performance of the wet air power generation fabric and the power generation composite parameter show a nonlinear relationship that first increases and then decreases, that is, as the value of the power generation composite parameter increases, the power generation performance of the wet air power generation fabric first increases and then decreases; by controlling and adjusting the power generation composite parameter, the power generation performance of the wet air power generation fabric can be quantitatively controlled and adjusted; the power generation composite parameter is the product of the stable power generation time and the sum of the relative humidity and temperature under the same weight, and the quotient of the difference in water evaporation on both sides of the coupling interface.
[0042] The moisture-generating fabric provided in the first aspect of the embodiment of the present application is modified with a conductive and hydrophilic reinforcing material on the surface of the fabric substrate to improve the hydrophilicity and conductivity of the fabric substrate. Then, a hygroscopic power generation functional material including a hygroscopic base material, a charge transfer material, a proton dissociation material and an antifreeze material is loaded on the coated area 2 of the modified fabric substrate. On the one hand, in the coated area 2 of the modified fabric substrate, a gel-like hygroscopic power generation functional material is formed by the synergistic effect of the hygroscopic base material, the charge transfer material, the proton dissociation material and the antifreeze material. The diffusion barrier of protons in the chromatographic mass transfer process is reduced by the charge transfer effect and the ion occupation effect, thereby improving the proton transfer efficiency. The hygroscopic power generation functional material with strong hygroscopicity and the flexible fabric with weak hygroscopicity are coupled, and the permanent asymmetric hygroscopicity difference on both sides of the coupling interface is used as a stable driving force for proton transfer, thereby achieving a long-lasting, stable and sustainable output of electrical performance, effectively solving the problem that traditional moisture power generation materials cannot generate electricity stably for a long time in changing weather conditions. On the other hand, with fabric as the substrate, the fabric has good flexibility and does not require additional packaging of hard electrodes, so it has good flexibility and air permeability, effectively breaking through the limitations of traditional moisture power generation materials that are difficult to apply in the wearable field. The moisture power generation fabric of the embodiment of the present application is based on the basic principle of moisture power generation. It uses the hydroxyl, carboxyl, sulfonic acid and other hygroscopic groups on the surface of the fabric substrate, especially the surface of the hygroscopic power generation functional material loaded in the coating area 2, to spontaneously absorb water molecules from the environment and dissociate a large number of protons after contact with water molecules. The water gradient constructed by the coated area 2 and the uncoated area 1 of the fabric substrate can make these positively charged internal protons spontaneously migrate in a directional manner, forming an electric field inside the material, thereby forming a stable external electrical output. In addition, the moisture power generation fabric of the present application does not require additional mechanical energy, temperature difference, light and other conditions. It can achieve energy conversion and electrical output only by relying on moisture in the environment. Therefore, it can be used as an all-weather power source to power wearable electronic products at any time and any place. In addition, the power generation performance of the moisture power generation fabric in the embodiment of the present application is determined by the power generation composite parameter (that is, the product of the stable power generation time and the relative humidity and temperature of the environment under the same weight, and the quotient of the difference in water evaporation on both sides of the coupling interface). That is, as the value of the power generation composite parameter increases, the power generation performance of the moisture power generation fabric first increases and then decreases. Therefore, by adjusting the power generation composite parameter, the power generation performance of the moisture-induced all-weather sustainable power generation fabric can be quantitatively controlled and optimized.
[0043] The embodiment of the present application is based on the fact that the moisture power generation effect is very complex. In addition to being related to the hygroscopic properties of the material, the relative humidity and temperature of the environment in which the material is located also directly affect the moisture power generation performance of the material. Among them, the greater the relative humidity of the environment, the stronger the moisture absorption capacity of the material, which makes the migration of protons inside the material stronger and the moisture power generation effect stronger. In addition, the moisture power generation effect requires a suitable ambient temperature, but too high a temperature will weaken the hygroscopic properties of the material, and too low a temperature will inhibit the migration of protons driven by water molecules, both of which will reduce the moisture power generation effect. Based on this, the embodiment of the present application proposes a composite power generation parameter. In some possible implementations, the power generation performance of the moisture power generation fabric provided by the embodiment of the present application is determined by the composite power generation parameter D: Wherein, T is the stable power generation time, in h; H is the relative humidity of the environment, in %; t is the ambient temperature, in °C; t min is the minimum power generation temperature, in °C; t max is the maximum power generation temperature, in °C; D0 is the difference in the natural evaporation of water per hour between the coated area 2 and the uncoated area 1, in mg. In some embodiments, t min -30℃, t max The temperature is 50°C and D0 is determined as the difference between the mass change of the coated area and the mass change of the uncoated area per hour.
[0044] In the power generation composite parameter D of the moisture power generation fabric in the embodiment of the present application, the power generation performance per unit time is directly related to temperature and humidity, and the two have considerable weights. Therefore, an addition process is performed. In order to adjust the weights of humidity and temperature to the same range of variation (i.e., between 0-100), the conversion is performed based on temperature. With the help of the minimum power generation temperature t min and the maximum power generation temperature t max The calculation limits the temperature t to the range of 0-100. Based on the above variables, DC power generation time is the key parameter for evaluating power generation performance. Multiplying this time by the influencing factors per unit time is used to control overall power generation performance. However, due to differences in the inherent properties of the materials, there is a fundamental difference in water evaporation between the coated area 2 and the uncoated area 1. While this difference promotes water transfer and increases power generation performance, to improve the accuracy of the power generation composite parameter control of the power generation performance of the moisture-generating fabric, the effect of this difference in water evaporation is normalized to obtain power generation performance per unit evaporation.
[0045] The power generation performance of the moisture-generating textile in the present embodiment is determined by the power generation composite parameter D. As the value of the power generation composite parameter increases, the power generation performance of the moisture-generating textile first increases and then decreases. Therefore, by adjusting the power generation composite parameter D, the power generation performance of the moisture-generating textile, which is sustainable and induced by all weather, can be quantitatively controlled and optimized. By varying the power generation composite parameter D, the electrical properties of the moisture-generating textile, such as its open-circuit voltage and short-circuit current, can be adjusted. Therefore, by adjusting the power generation composite parameter, the power generation performance of the moisture-generating textile, which is sustainable and induced by all weather, can be quantitatively controlled and optimized.
[0046] In some possible implementations, the fabric substrate includes at least one of polypropylene, polyester, polyacrylonitrile, viscose, acrylic, polyamide, wool, linen, and silk. These materials used in the fabric substrates of the present application embodiments all have good flexibility and breathability, improving the wearability of the moisture-generating fabric.
[0047] In some possible implementations, after obtaining the fabric substrate, the fabric substrate is cut, and the size is extended in one direction, with the longer direction as the length and the shorter direction as the width, and the fabric substrate is cut into a rectangle. In some embodiments, the ratio of the length and width of the fabric substrate is (1 to 8): 1. Under this length-to-width ratio, it is beneficial to subsequently divide the relative coating area 2 and uncoated area 1 on the surface of the fabric substrate, and also to make the fabric substrate have a suitable internal resistance size, avoiding an excessively large aspect ratio, an excessively large electron transmission path, and an excessively high internal resistance. Exemplarily, the ratio of the length and width of the fabric substrate can be 1: 1, 2: 1, 3: 1, 4: 1, 5: 1, 6: 1, 7: 1, 8: 1, etc. In some specific embodiments, the ratio of the length and width of the fabric substrate is preferably 4: 1.
[0048] In some possible implementations, the fabric substrate is rectangular with a length-to-width ratio of (1-8):1. The coated region 2 and the uncoated region 1 are distributed along the length of the fabric substrate, that is, the fabric substrate is divided into opposing coated regions 2 and uncoated regions 1 along the length of the fabric substrate. In this case, it is more conducive to establishing a water gradient based on the difference in water absorption properties between the uncoated region 1 and the coated region 2 on the surface of the fabric substrate. This utilizes moisture in the air to induce spontaneous directional migration of protons within the material, resulting in a stable external electrical output.
[0049] In order to make the hydrophilicity and conductivity of the fabric base meet the requirements of moisture power generation fabrics, the surface of the fabric base is modified with conductive and hydrophilic reinforcing materials, so that the fabric base has suitable water absorbency and good conductivity, which is conducive to the moisture power generation fabric absorbing moisture in the environment and converting it into protons during use, and improving the directional movement of positively charged protons inside the fabric base, forming an electric field inside the material, thereby forming a stable external electrical output.
[0050] In some possible implementations, the reinforcing material includes a carbon material and a surfactant; wherein the carbon material can improve the conductivity and hydrophilicity of the fabric substrate, and the surfactant can improve the dispersion performance of the carbon material, reduce the agglomeration of the carbon material, and make the carbon material uniformly and stably modified on the surface of the fabric substrate.
[0051] In some possible implementations, the carbon material includes at least one of carbon black, graphene, graphene oxide, graphite, and carbon nanotubes; each of these carbon materials has excellent electrical conductivity and, when modified on the surface of a fabric substrate, can impart good electrical conductivity and hydrophilicity to the fabric substrate. In some specific embodiments, the carbon material is selected from carbon black.
[0052] In some possible implementations, the surfactant includes at least one of alkylbenzene sulfonate, alkyl sulfonate ester, alkyl sulfonate, alkyl sulfate, olefin sulfonate, and cycloalkane salt; all of these surfactants can effectively improve the dispersion properties of the carbon material. In some specific embodiments, the surfactant includes sodium lauryl sulfate.
[0053] In some possible implementations, the mass ratio of carbon material to surfactant is (0.8-1.2):1. Under this ratio, it ensures that the carbon material has good dispersion properties, reduces the agglomeration of carbon materials, and makes the carbon material evenly modified on the surface of the fabric, thereby improving the conductivity and hydrophilicity of the fabric substrate. It is also beneficial for the modification of the fabric substrate by the reinforcing material containing carbon material and surfactant. Exemplarily, the mass ratio of carbon material to surfactant can be 0.8:1, 0.9:1, 1:1, 1.1:1, 1.2:1, etc. In some specific embodiments, the mass ratio of carbon material to surfactant is 1:1.
[0054] In some possible implementations, the surface of the modified fabric substrate has a water contact angle of less than 90 degrees and a sheet resistance of less than 100 Ω / sq. In embodiments of the present application, after the surface of the fabric substrate is modified with conductive and hydrophilic reinforcing materials, the modified fabric substrate material exhibits both good conductivity and hydrophilicity, with a water contact angle of less than 90 degrees and a sheet resistance of less than 100 Ω / sq.
[0055] In some possible implementations, the hygroscopic base material of the hygroscopic power generation functional material includes polyvinyl alcohol. In this case, the hygroscopic base material exhibits advantages such as high hygroscopicity, good water solubility, strong adjustability, good stability, and environmental friendliness. It can rapidly absorb moisture from the surrounding environment, exhibiting a high rate and capacity of moisture absorption. Furthermore, through synergistic effects with other components, the hygroscopic power generation functional material can form a gel state and be stably loaded onto the surface of the modified fabric substrate. Furthermore, by varying the degree of polymerization, crosslinking, and hydrophilicity of the polyvinyl alcohol, its hygroscopic properties can be adjusted, enabling the polyvinyl alcohol to provide appropriate hygroscopic properties in varying humidity environments.
[0056] In some possible implementations, the charge transfer material in the hygroscopic power generation functional material includes at least one of calcium chloride and lithium chloride. In this case, these charge transfer materials utilize their hydration capacity to form hydrates through moisture absorption and the release and binding of ions, thereby achieving the charge transfer process. These charge transfer materials all have good hydration capacity, meaning they can absorb moisture from the surrounding environment to form hydrates. This hydration process involves the release and binding of ions, resulting in charge transfer. When the humidity in the air is high, calcium chloride and lithium chloride can absorb moisture from the air to form hydrates and release ions. The released ions can induce charge transfer in the functional groups of the proton dissociation material, promoting the dissociation and release of protons. At the same time, these ions have a stronger binding ability to the proton dissociation sites than protons, effectively preventing the recombination of dissociated protons with the dissociation sites. This ion occupation effect reduces the diffusion barrier of protons during mass transfer and improves proton transfer efficiency.
[0057] In some possible implementations, the proton dissociation material in the hygroscopic power generation functional material includes at least one of poly (4-styrene sulfonic acid) and poly (2-acrylamide-2-methyl-1-propanesulfonic acid); in this case, these proton dissociation materials all contain proton-active functional groups such as sulfonic acid groups, and achieve proton dissociation and transmission through hydration, ion exchange, and high plasma formation. Specifically, these proton dissociation materials contain sulfonic acid groups (-SO3H), which can easily lose a proton (H + ) and form negative ions (polyions).
[0058] In some possible implementations, the antifreeze material in the moisture-absorbing power generation functional material includes glycerin. In this case, using glycerin as the antifreeze material can lower the freezing point, increase heat capacity, and improve freeze-thaw cycle resistance, thereby improving the low-temperature resistance of the moisture-generating textile, enabling it to operate in relatively low ambient temperatures.
[0059] In some possible implementations, the ratio of the hygroscopic base material, charge transfer material, proton dissociation material, antifreeze material, and water in the hygroscopic power generation material is (1.0-2.0) g: (0.05-0.5) g: (1.5-3.0) g: (0.1-5) mL: 10 mL. This ratio ensures sufficient viscosity and fluidity for the hygroscopic power generation material, facilitating subsequent loading of the hygroscopic power generation material onto the surface of the fabric substrate through coating or other methods. For example, in the hygroscopic power generation functional material, the ratio of the hygroscopic base material, the charge transfer material, the proton dissociation material, the antifreeze material and water can be 1.0g: (0.05-0.5)g: (1.5-3.0)g: (0.1-5)mL: 10mL, 1.2g: (0.05-0.5)g: (1.5-3.0)g: (0.1-5)mL: 10mL, 1.4g: (0.05-0.5)g: (1.5-3.0)g: (0.1-5)mL: 10mL, 1.6g: (0.05-0.5)g: (1 .5~3.0)g: (0.1~5)mL: 10mL, 1.8g: (0.05~0.5)g: (1.5~3.0)g: (0.1~5)mL: 10mL, 2.0g: (0.05~0.5)g: (1.5~3.0)g: (0. 1~5)mL: 10mL, (1.0~2.0)g: 0.05g: 1.8g: (0.1~5)mL: 10mL, (1.0~2.0)g: 0.1g: 1.8g: (0.1~5)mL: 10mL, (1.0~2.0)g: 0.2 g: 1.8g: (0.1~5)mL: 10mL, (1.0~2.0)g: 0.3g: 1.8g: (0.1~5)mL: 10mL, (1.0~2.0)g: 0.4g: 1.8g: (0.1~5)mL: 10mL, (1.0 ~2.0)g: 0.5g: 1.8g: (0.1~5)mL: 10mL, (1.0~2.0)g: (0.05~0.5)g: 1.8g: 0.1mL: 10mL, (1.0~2.0)g: (0.05~0.5)g: 1.8g: 0.5mL: 10mL, (1.0~2.0)g: (0.05~0.5)g: 1.8g: 1mL: 10mL, (1.0~2.0)g: (0.05~0.5)g: 1.8g: 2mL: 10mL, (1.0~2.0)g: (0 .05~0.5)g: 1.8g: 3mL: 10mL, (1.0~2.0)g: (0.05~0.5)g: 1.8g: 4mL: 10mL, (1.0~2.0)g: (0.05~0.5)g: 1.8g: 5mL: 10mL, etc.
[0060] In some possible implementations, the hygroscopic power generation material includes polyvinyl alcohol, lithium chloride, poly (4-styrene sulfonic acid) solution, and glycerol, wherein the mass concentration of the poly (4-styrene sulfonic acid) solution is 15% to 30%. In this case, the ratio of polyvinyl alcohol, lithium chloride, poly (4-styrene sulfonic acid) solution, and glycerol in the hygroscopic power generation material is (1.0-2.0) g: (0.05-0.5) g: 10 mL: (0.1-5) mL.
[0061] In some possible implementations, in the coating area 2, the loading amount of the hygroscopic power generation functional material is 0.1 mL / cm 2 ~0.5mL / cm 2 In this case, the loading amount of the hygroscopic power generation functional material in the coating area 2 of the modified fabric substrate fully ensures the loading effect, which can better improve the power generation performance of the moisture power generation fabric. For example, in the coating area 2, the loading amount of the hygroscopic power generation functional material can be 0.1mL / cm 2 , 0.2mL / cm 2 , 0.3mL / cm 2 , 0.4mL / cm 2 , 0.5mL / cm 2 wait.
[0062] In some possible implementations, in the wet air power generation fabric, the area ratio of the coated area 2 to the uncoated area 1 is (1 to 9):3. In this case, the higher the area ratio of the coated area 2, the more hygroscopic power generation functional material is loaded, which is more conducive to improving the power generation performance. However, it is also necessary to retain enough uncoated areas 1 and coated areas 2 to build a water gradient, form an electric current through the directional migration of internal protons, and realize the power generation function. Exemplarily, in the wet air power generation fabric, the area ratio of the coated area 2 to the uncoated area 1 can be 1:3, 2:3, 3:3, 4:3, 5:3, 6:3, 7:3, 8:3, 9:3, etc. In some specific embodiments, in the wet air power generation fabric, the area ratio of the coated area 2 to the uncoated area 1 is 3:3.
[0063] In some possible implementations, the moisture-generating fabric is connected to an electrical collector or consumer, with the coated region 2 connected to the negative electrode and the uncoated region 1 connected to the positive electrode. In the moisture-generating fabric of the present application, the coated region 2 is loaded with a gel-like hygroscopic, power-generating functional material. This material absorbs moisture from the environment and dissociates to release positively charged hydrogen ions. These hydrogen ions migrate from the coated region 2 to the uncoated region 1 as the water diffuses, forming a continuous current and manifesting as a stable external electrical output. Therefore, the coated region 2 acts as the negative electrode, connected to the negative electrode of the electrical collector or consumer; the uncoated region 1 acts as the positive electrode, connected to the positive electrode of the electrical collector or consumer.
[0064] In some embodiments, the electrical collection device may be a capacitor or the like.
[0065] In some embodiments, the electrical device may be an LED lamp, an electronic watch, a calculator, etc.
[0066] In a second aspect, the present invention provides a method for preparing the above-mentioned moisture power generation fabric, as shown in the attached Figure 2 As shown, the following steps are included:
[0067] S10 obtains a fabric substrate, and modifies the surface of the fabric substrate with a conductive and hydrophilic reinforcing material to obtain a modified fabric substrate;
[0068] S20. Preparation of a hygroscopic power generation functional material including a hygroscopic base material, a charge transfer material, a proton dissociation material and an antifreeze material;
[0069] S30. Dividing the surface of the modified fabric substrate into a coated area 2 and an uncoated area 1 relative to each other, loading the coated area 2 with a gel-state hygroscopic power generation functional material to obtain a moisture power generation fabric.
[0070] The method for preparing a moisture-generating fabric in an embodiment of the present application uses a fabric as a substrate, exhibits excellent flexibility and breathability, and can be directly applied in wearable applications. The surface of the fabric substrate is modified with a conductive and hydrophilic reinforcing material to improve the hydrophilicity and conductivity of the fabric substrate. After the modified surface of the fabric substrate is divided into a coated area 2 and an uncoated area 1, the coated area 2 is loaded with a hygroscopic, power-generating functional material comprising a hygroscopic base material, a charge transfer material, a proton dissociation material, and an antifreeze material, thereby producing a moisture-generating fabric. The preparation process is simple and suitable for large-scale commercial production and application. The moisture-generating fabric in this application requires no additional mechanical energy, temperature differences, or light, relying solely on ambient moisture to achieve energy conversion and electrical output. The coated area 2 on the fabric substrate surface contains a large number of hygroscopic groups that spontaneously absorb water molecules from the environment and, upon contact with the water molecules, dissociate a large number of protons. This creates a water gradient between the coated area 2 and the uncoated area 1, causing these positively charged internal protons to spontaneously migrate in a directional manner, forming an electric field within the material, thereby generating a stable external electrical output.
[0071] In some possible implementations, in the above-mentioned step S10, the step of modifying the reinforcing material on the surface of the fabric substrate includes: impregnating and drying the fabric substrate with a mixed solution including a carbon material and a surfactant to obtain a modified fabric substrate. In the embodiment of the present application, the carbon material and the surfactant are dissolved in a solvent to prepare a mixed solution, and then the fabric substrate is impregnated and dried so that the carbon material and the surfactant are stably bound to the surface of the fabric substrate. In some embodiments, the fabric substrate is impregnated and dried 1 to 10 times with a mixed solution including a carbon material and a surfactant, that is, the fabric substrate is immersed in the mixed solution and dried, and then immersed in the mixed solution for a second immersion and then dried, and this is repeated 2 to 9 times to ensure the modification effect of the reinforcing material on the fabric substrate.
[0072] In some possible implementations, the material of the fabric base includes at least one of polypropylene, polyester, polyacrylonitrile, viscose fiber, acrylic, polyamide, wool, linen, and silk; these materials all have good flexibility and breathability, which improves the wearability of the moisture-generating fabric.
[0073] In some possible implementations, after obtaining the fabric base, the fabric base is cut to a length and width ratio of (1 to 8):1, and the coated area 2 and the uncoated area 1 are distributed along the length direction of the fabric base.
[0074] In some possible implementations, the carbon material includes at least one of carbon black, graphene, graphene oxide, graphite, and carbon nanotubes; these carbon materials all have excellent electrical conductivity and hydrophilicity, and modification on the surface of the fabric substrate can make the fabric substrate have better conductivity.
[0075] In some possible implementations, the surfactant includes at least one of alkylbenzene sulfonate, alkyl sulfonate ester, alkyl sulfonate, alkyl sulfate, olefin sulfonate, and cycloalkane salt; all of these surfactants can effectively improve the dispersion properties of the carbon material. In some specific embodiments, the surfactant includes sodium lauryl sulfate.
[0076] In some possible implementations, the mass ratio of carbon material to surfactant is (0.8-1.2):1; this ratio ensures that the carbon material has good dispersion properties, reduces the agglomeration of carbon materials, and allows the carbon material to be evenly modified on the fabric surface, thereby improving the conductivity and hydrophilicity of the fabric substrate; it is also beneficial to the modification operation of the fabric substrate by the reinforcing material containing carbon material and surfactant.
[0077] In some possible implementations, the surface water contact angle of the modified fabric substrate is less than 90°, and the sheet resistance is less than 100Ω / sq; the modified fabric substrate material has both good electrical conductivity and hydrophilicity.
[0078] In some possible implementations, in the above-mentioned step S20, in the hygroscopic power generation functional material, the hygroscopic base material includes polyvinyl alcohol; the hygroscopic base material has the advantages of high hygroscopic performance, good water solubility, strong adjustability, good stability and environmental protection, and can quickly absorb moisture in the surrounding environment, and has a high hygroscopic speed and hygroscopic capacity.
[0079] In some possible implementations, the charge transfer material in the hygroscopic power generation functional material includes at least one of calcium chloride and lithium chloride. These charge transfer materials utilize their hydration capacity and ionic conductivity to achieve charge transfer through moisture absorption, hydrate formation, and ion release and binding. These charge transfer materials all have good hydration capacity, meaning they can absorb moisture from the surrounding environment to form hydrates. This hydration process involves the release and binding of ions, leading to charge transfer. When the humidity in the air is high, calcium chloride and lithium chloride can absorb moisture from the air to form hydrates and release ions. The released ions can induce charge transfer in the functional groups of the proton dissociation material, promoting the dissociation and release of protons. At the same time, these ions have a stronger binding ability to the proton dissociation sites than protons, effectively preventing the recombination of dissociated protons with the dissociation sites. This ion occupation effect reduces the diffusion barrier of protons during mass transfer and improves proton transfer efficiency.
[0080] In some possible implementations, in the hygroscopic power generation functional material, the proton dissociation material includes at least one of poly (4-styrene sulfonic acid) and poly (2-acrylamide-2-methyl-1-propanesulfonic acid); these proton dissociation materials all contain proton-active functional groups such as sulfonic acid groups, and these proton-active functional groups can easily lose a proton (H + ) and form negative ions (polyions), achieving proton dissociation and transport through hydration, ion exchange and high plasma.
[0081] In some possible implementations, the antifreeze material in the hygroscopic power generation functional material includes glycerol. Using glycerol as the antifreeze material can lower the freezing point, increase heat capacity and resistance to freeze-thaw cycles, thereby improving the low-temperature resistance of the moisture-absorbing power generation fabric and enabling it to operate at relatively low ambient temperatures.
[0082] In some specific embodiments, the hygroscopic base material includes polyvinyl alcohol; the charge transfer material includes calcium chloride and / or lithium chloride; the proton dissociation material includes poly (4-styrene sulfonic acid) and / or poly (2-acrylamide-2-methyl-1-propanesulfonic acid); and the antifreeze material includes glycerol.
[0083] In some possible implementations, the ratio of the hygroscopic base material, charge transfer material, proton dissociation material, antifreeze material, and water in the hygroscopic power generation material is (1.0-2.0) g: (0.05-0.5) g: (1.5-3.0) g: (0.1-5) mL: 10 mL. This ratio ensures sufficient viscosity and fluidity for the hygroscopic power generation material, facilitating subsequent loading of the hygroscopic power generation material onto the surface of the fabric substrate through coating or other methods.
[0084] In some possible implementations, in the above step S30, the step of loading the hygroscopic power generation functional material on the coating area 2 includes: coating the hygroscopic power generation functional material at a coating amount of 0.1 mL / cm 2 ~0.5mL / cm 2 Coated to the coating area 2; in this case, the loading amount of the hygroscopic power generation functional material in the coating area 2 of the modified fabric substrate fully ensures the loading effect, which can better improve the power generation performance of the moisture power generation fabric.
[0085] In some possible implementations, in the moisture power generation fabric, the area ratio of the coated area 2 to the uncoated area 1 is (1 to 9):3; in this case, the area ratio of the coated area 2 is relatively high, and the loaded hygroscopic power generation functional materials are more conducive to improving the power generation performance. At the same time, sufficient uncoated areas 1 and coated areas 2 are retained to construct a water gradient, forming an electric current through the directional migration of internal protons to realize the power generation function.
[0086] In some embodiments, after the surface of the modified fabric substrate is divided into a coated area 2 and an uncoated area 1 along the length direction, the hygroscopic power generation functional material is coated on the coated area 2 of the modified fabric substrate surface within an area of 1 / 4 to 3 / 4 along the length direction from one end, and the coating amount of the hygroscopic power generation functional material in the coated area 2 is 0.1 to 0.5 mL / cm 2 Then, it was placed under vacuum conditions at 50°C for 24 hours to allow the moisture-absorbing power generation functional material to form a stable gel state loaded on the surface of the modified fabric substrate to obtain moisture-generating fabric.
[0087] In some possible implementations, the coated area 2 of the moisture-generating textile serves as the negative electrode, while the uncoated area 1 serves as the positive electrode. Because the coated area 2 is loaded with a gel-like hygroscopic, power-generating material, this material absorbs moisture from the environment and dissociates, releasing positively charged hydrogen ions. These hydrogen ions diffuse with the water, migrating from the coated area 2 to the uncoated area 1, forming a continuous current and manifesting as a stable external electrical output. Therefore, the coated area 2 serves as the negative electrode, connected to the positive electrode of a power-collecting or power-consuming device; the uncoated area 1 serves as the positive electrode, connected to the positive electrode of the power-collecting or power-consuming device.
[0088] In a third aspect, an embodiment of the present application provides an application of a moisture-generating fabric, wherein the moisture-generating fabric or the moisture-generating fabric prepared by the above method is applied to a moisture-induced power generation device.
[0089] The moisture-generating textiles described in the embodiments of the present application do not require additional mechanical energy, temperature differences, or light, relying solely on ambient moisture to achieve energy conversion and electrical output. Therefore, the moisture-generating textiles can be applied to moisture-induced power generation devices. They can serve as an all-weather power source for wearable electronics and other devices at any time and in any location.
[0090] In order to make the above implementation details and operations of this application clearly understood by those skilled in the art, as well as to significantly demonstrate the advanced performance of the moisture-generating fabrics and their preparation methods and applications in the embodiments of this application, the above technical solutions are illustrated by multiple embodiments below.
[0091] Example 1
[0092] A moisture power generation fabric, the preparation of which comprises the following steps:
[0093] ① Cut the polyacrylonitrile fiber nonwoven fabric into a rectangle with an aspect ratio of 1:1, soak and wash it with deionized water and ethanol respectively to remove surface impurities, and dry it at 60℃ to constant weight.
[0094] ② Disperse 0.4 g of carbon black and 0.5 g of sodium dodecyl sulfate in 100 mL of deionized water and ultrasonically treat for 5 minutes to mix the components evenly to obtain a carbon black impregnation solution for modifying the fabric; then immerse the cleaned fabric in the carbon black impregnation solution for 5 minutes, take it out and dry it at 60°C to constant weight, repeat the above immersion-drying operation once to obtain a carbon black modified fabric.
[0095] ③ 1.0 g of polyvinyl alcohol, 0.05 g of lithium chloride, 10 mL of poly (4-styrene sulfonic acid) solution (mass concentration 15%), and 0.1 mL of glycerol were mixed evenly and stirred at 90°C for 60 min to obtain a hygroscopic power generation functional material; a certain amount of the hygroscopic power generation functional material was coated on 1 / 4 of the area starting from one end along the length direction of the carbon black modified fabric, and the coating amount of the hygroscopic power generation functional material in the coating area 2 was 0.1 mL / cm 2 Then, it was placed under vacuum conditions at 50°C for 24 hours to allow the moisture-absorbing power generation functional material to form a stable gel state loaded on the surface of the carbon black modified fabric to obtain moisture-generating fabric.
[0096] As attached Figure 3 and attached Figure 4As shown, the uncoated area 1 on the moisture power generation fabric is used as the positive electrode, and the coated area 2 is used as the negative electrode. The positive and negative electrodes of the moisture power generation fabric are connected to the positive and negative electrodes of the electrical collector 31 or the electrical device 32 respectively by wires to realize the collection of electrical energy or drive the electrical device to operate.
[0097] The uncoated area 1 on the moisture power generation fabric was used as the positive electrode, and the coated area 2 was used as the negative electrode. The positive and negative electrodes of the moisture power generation fabric were connected to the positive and negative electrodes of the electrometer using wires. Under the environmental conditions of temperature 20°C-35°C and relative humidity 45%-75%, the open circuit voltage and short circuit current were measured and recorded once every 24 hours. The open circuit voltage and short circuit current data recorded by the electrometer in Example 1 are shown in the attached figure. Figure 5 As shown, the experimental results show that the prepared moisture-generating fabric can generate electricity stably for more than 15 days under the conditions of ambient relative humidity of 45%-75% and ambient temperature of 20℃-35℃, that is, it has all-weather sustainable power generation effect.
[0098] The uncoated area 1 on the moisture power generation fabric was used as the positive electrode, and the coated area 2 was used as the negative electrode. The positive and negative electrodes of the moisture power generation fabric were connected to the positive and negative electrodes of the electrometer respectively using wires to obtain the power generation under different D values. The power generation when D = 0 was used as the basic value to calculate the power generation change rate under other D values. Example 1 The change rate of the electrical performance of the moisture power generation fabric with the adjustment of the power generation composite parameters is shown in the attached figure. Figure 6 As shown in the test results, when the power generation composite parameter D is 180 (at this time, T = 360h, H = 65, t = 20℃, t min =-30℃, t max =50℃, D0=255) the electrical performance of the moisture-generating fabric is the best.
[0099] Example 2
[0100] A moisture power generation fabric, the preparation of which comprises the following steps:
[0101] ① Cut the polyester fiber non-woven fabric into a rectangle with an aspect ratio of 4:1, soak and clean it with deionized water and ethanol respectively to remove surface impurities, and dry it at 60℃ to constant weight.
[0102] ② Disperse 0.5 g of carbon black and 0.5 g of sodium dodecyl sulfate in 100 mL of deionized water and ultrasonically treat for 5 minutes to mix the components evenly to obtain a carbon black impregnation solution for modifying the fabric; then immerse the cleaned fabric in the carbon black impregnation solution for 5 minutes, take it out and dry it at 60°C to constant weight. Repeat the above immersion-drying operation 4 times to obtain a carbon black modified fabric.
[0103] ③ 1.5 g of polyvinyl alcohol, 0.2 g of lithium chloride, 10 mL of poly (4-styrene sulfonic acid) solution (mass concentration 18%), and 2 mL of glycerol were mixed evenly and stirred at 90°C for 60 min to obtain a hygroscopic power generation functional material; a certain amount of the hygroscopic power generation functional material was coated on 1 / 2 of the area starting from one end along the length direction of the carbon black modified fabric, and the coating amount of the hygroscopic power generation functional material in the coating area 2 was 0.2 mL / cm 2 Then, it was placed under vacuum conditions at 50°C for 24 hours to allow the moisture-absorbing power generation functional material to form a stable gel state loaded on the surface of the carbon black modified fabric to obtain moisture-generating fabric.
[0104] As attached Figure 7 and attached Figure 8 As shown, the uncoated area 1 on the moisture power generation fabric is used as the positive electrode, and the coated area 2 is used as the negative electrode. The positive and negative electrodes of the moisture power generation fabric are connected to the positive and negative electrodes of the electrical collector 31 or the electrical device 32 respectively by wires to realize the collection of electrical energy or drive the electrical device to operate.
[0105] The uncoated area 1 on the moisture power generation fabric was used as the positive electrode, and the coated area 2 was used as the negative electrode. The positive and negative electrodes of the moisture power generation fabric were connected to the positive and negative electrodes of the electrometer using wires. Under the environmental conditions of temperature 20°C-35°C and relative humidity 45%-75%, the open circuit voltage and short circuit current were measured and recorded once every 24 hours. The open circuit voltage and short circuit current data recorded by the electrometer in Example 2 are shown in the attached figure. Figure 9 As shown, the experimental results show that the prepared moisture-generating fabric can generate electricity stably for more than 15 days under the conditions of ambient relative humidity of 45%-75% and ambient temperature of 20℃-35℃, that is, it has all-weather sustainable power generation effect.
[0106] The uncoated area 1 on the moisture power generation fabric was used as the positive electrode, and the coated area 2 was used as the negative electrode. The positive and negative electrodes of the moisture power generation fabric were connected to the positive and negative electrodes of the electrometer respectively using wires to obtain the power generation under different D values. The power generation when D = 0 was used as the basic value to calculate the power generation change rate under other D values. Example 2 The change rate of the electrical performance of the moisture power generation fabric with the adjustment of the power generation composite parameters is shown in the attached figure. Figure 10 As shown in the test results, when the power generation composite parameter D is 180 (at this time, T = 360h, H = 65, t = 20℃, t min =-30℃, t max =50℃, D0=255) the electrical performance of the moisture-generating fabric is the best.
[0107] Example 3
[0108] A moisture power generation fabric, the preparation of which comprises the following steps:
[0109] ① Cut the polypropylene fiber non-woven fabric into a rectangle with an aspect ratio of 8:1, soak and clean it with deionized water and ethanol respectively to remove surface impurities, and dry it at 60℃ to constant weight.
[0110] ② Disperse 0.6 g of carbon black and 0.5 g of sodium dodecyl sulfate in 100 mL of deionized water and ultrasonically treat for 5 minutes to mix the components evenly to obtain a carbon black impregnation solution for modifying the fabric; then immerse the cleaned fabric in the carbon black impregnation solution for 5 minutes, take it out and dry it at 60°C to constant weight. Repeat the above immersion-drying operation 10 times to obtain a carbon black modified fabric.
[0111] ③ 2.0 g of polyvinyl alcohol, 0.5 g of lithium chloride, 10 mL of poly (4-styrene sulfonic acid) solution (mass concentration 30%), and 5 mL of glycerol were mixed evenly and stirred at 90°C for 60 min to obtain a hygroscopic power generation functional material; a certain amount of the hygroscopic power generation functional material was coated on 3 / 4 of the area of the carbon black modified fabric starting from one end along the length direction, and the coating amount of the hygroscopic power generation functional material in the coating area 2 was 0.5 mL / cm 2 Then, it was placed under vacuum conditions at 50°C for 24 hours to allow the moisture-absorbing power generation functional material to form a stable gel state loaded on the surface of the carbon black modified fabric to obtain moisture-generating fabric.
[0112] As attached Figure 11 and attached Figure 12 As shown, the uncoated area 1 on the moisture power generation fabric is used as the positive electrode, and the coated area 2 is used as the negative electrode. The positive and negative electrodes of the moisture power generation fabric are connected to the positive and negative electrodes of the electrical collector 31 or the electrical device 32 respectively by wires to realize the collection of electrical energy or drive the electrical device to operate.
[0113] The uncoated area 1 on the moisture power generation fabric was used as the positive electrode, and the coated area 2 was used as the negative electrode. The positive and negative electrodes of the moisture power generation fabric were connected to the positive and negative electrodes of the electrometer using wires. Under the environmental conditions of temperature 20°C-35°C and relative humidity 45%-75%, the open circuit voltage and short circuit current were measured and recorded once every 24 hours. The open circuit voltage and short circuit current data recorded by the electrometer in Example 3 are shown in the attached figure. Figure 13 As shown, the experimental results show that the prepared moisture-generating fabric can generate electricity stably for more than 15 days under the conditions of ambient relative humidity of 45%-75% and ambient temperature of 20℃-35℃, that is, it has all-weather sustainable power generation effect.
[0114] The uncoated area 1 on the moisture power generation fabric was used as the positive electrode, and the coated area 2 was used as the negative electrode. The positive and negative electrodes of the moisture power generation fabric were connected to the positive and negative electrodes of the electrometer respectively using wires to obtain the power generation under different D values. The power generation when D = 0 was used as the basic value to calculate the power generation change rate under other D values. Example 3 The change rate of the electrical performance of the moisture power generation fabric with the adjustment of the power generation composite parameters is shown in the attached figure. Figure 14 As shown in the test results, when the power generation composite parameter D is 180 (at this time, T = 360h, H = 65, t = 20℃, t min =-30℃, t max =50℃, D0=255) the electrical performance of the moisture-generating fabric is the best.
[0115] By the above attachment Figure 5 , Attachment Figure 9 and attached Figure 13 It can be seen from the power generation performance data that the moisture power generation fabric prepared in this application can generate stable open circuit voltage and short circuit current under the conditions of ambient relative humidity of 45%-75% and ambient temperature of 20℃-35℃, and the electrical output performance can remain stable for at least 15 days, indicating that the moisture power generation fabric prepared in this application has excellent all-weather, sustainable and long-lasting power generation effect.
[0116] By the above attachment Figure 6 , Attachment Figure 10 and attached Figure 14 It can be seen from the change rate of the electrical performance with the adjustment of the power generation composite parameter that when the power generation composite parameter D is 180, the electrical performance of the moisture power generation fabric is the best and has the maximum electrical output.
[0117] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent replacements and improvements made within the spirit and principles of the present application should be included in the scope of protection of the present application.
Claims
1. A moisture power generation fabric, characterized in that: The invention comprises a fabric substrate, the surface of which is modified with a conductive and hydrophilic reinforcing material, wherein the modified surface of the fabric substrate comprises a coated area and an uncoated area relative to each other, wherein the coated area and the uncoated area form an asymmetric hygroscopic difference that drives proton transport; wherein the coated area is loaded with a gel-state hygroscopic power generation functional material, wherein the hygroscopic power generation functional material comprises a hygroscopic base material, a charge transfer material, a proton dissociation material, and an antifreeze material; and wherein the hygroscopic power generation functional material improves proton transport efficiency through a charge transfer effect and an ion occupation effect; The power generation performance of the wet air power generation fabric is determined by a power generation composite parameter, and the power generation performance of the wet air power generation fabric and the power generation composite parameter show a nonlinear relationship that first increases and then decreases, that is, as the value of the power generation composite parameter increases, the power generation performance of the wet air power generation fabric first increases and then decreases; by controlling and adjusting the power generation composite parameter, the power generation performance of the wet air power generation fabric is quantitatively controlled and adjusted; the power generation composite parameter is the product of the stable power generation time and the sum of the relative humidity and temperature under the same weight, and the quotient of the difference in water evaporation on both sides of the coupling interface.
2. The moisture power generation fabric according to claim 1, characterized in that: The material of the fabric base comprises at least one of polypropylene, polyester, polyacrylonitrile, viscose, acrylic, polyamide, wool, linen, and silk; And / or, the reinforcing material includes a carbon material and a surfactant; and / or, the hygroscopic base material comprises polyvinyl alcohol; And / or, the charge transfer material includes at least one of calcium chloride and lithium chloride; and / or, the proton dissociation material comprises at least one of poly (4-styrene sulfonic acid) and poly (2-acrylamide-2-methyl-1-propanesulfonic acid); And / or, the antifreeze material includes glycerol.
3. The moisture-generating fabric according to claim 2, wherein: The carbon material includes at least one of carbon black, graphene, graphene oxide, graphite, and carbon nanotubes; and / or, the surfactant comprises at least one of alkylbenzene sulfonate, alkyl sulfonate ester, alkyl sulfonate, alkyl sulfate, olefin sulfonate, and cycloalkaneate; And / or, the mass ratio of the carbon material to the surfactant is (0.8-1.2):
1.
4. The moisture power generation fabric according to any one of claims 1 to 3, characterized in that: In the hygroscopic power generation functional material, the hygroscopic base material, the charge transfer material, the proton dissociation material, the antifreeze material and water are mixed in a ratio of (1.0-2.0) g: (0.05-0.5) g: (1.5-3.0) g: (0.1-5) mL: 10 mL; And / or, the surface water contact angle of the modified fabric substrate is less than 90°, and the sheet resistance is less than 100Ω / sq; And / or, in the moisture power generation fabric, the area ratio of the coated area to the uncoated area is (1-9):
3.
5. The moisture power generation fabric according to claim 4, characterized in that: In the coating area, the loading amount of the hygroscopic power generation functional material is 0.1 mL / cm 2 ~0.5mL / cm 2 ; And / or, the ratio of the length to the width of the fabric base is (1-8):1, and the coated area and the uncoated area are distributed along the length direction of the fabric base.
6. The moisture power generation fabric according to claim 5, characterized in that: The moisture power generation fabric is connected to an electricity collecting device or an electricity consuming device, wherein the coated area is connected to a negative electrode, and the uncoated area is connected to a positive electrode.
7. A method for preparing the moisture power generation fabric according to any one of claims 1 to 6, characterized in that: The following steps are involved: Obtaining a fabric substrate, and modifying the surface of the fabric substrate with a reinforcing material having conductivity and hydrophilicity to obtain a modified fabric substrate; Formulating a hygroscopic power generation functional material comprising a hygroscopic base material, a charge transfer material, a proton dissociation material and an antifreeze material; The surface of the modified fabric substrate is divided into a coated area and an uncoated area relative to each other, and the gel-state hygroscopic power generation functional material is loaded on the coated area to obtain a moisture power generation fabric.
8. The method for preparing the moisture power generation fabric according to claim 7, wherein: The step of modifying the reinforcing material on the surface of the fabric substrate comprises: impregnating the fabric substrate with a mixed solution comprising a carbon material and a surfactant and drying the mixed solution to obtain the modified fabric substrate; And / or, the step of loading the hygroscopic power generation functional material on the coating area includes: applying the hygroscopic power generation functional material at a coating amount of 0.1 mL / cm 2 ~0.5mL / cm 2 applying to the coating area; and / or, the material of the fabric substrate comprises at least one of polypropylene, polyester, polyacrylonitrile, viscose, acrylic, polyamide, wool, linen, and silk; And / or, the hygroscopic base material comprises polyvinyl alcohol; the charge transfer material comprises calcium chloride and / or lithium chloride; the proton dissociation material comprises poly-4-styrene sulfonic acid and / or poly(2-acrylamide-2-methyl-1-propanesulfonic acid); the antifreeze material comprises glycerol; And / or, in the hygroscopic power generation functional material, the ratio of the hygroscopic base material, the charge transfer material, the proton dissociation material, and the antifreeze material is (1.0~2.0)g:(0.05~0.5)g:(1.5~3.0)g:(0.1~5)mL:10mL.
9. The method for preparing the moisture power generation fabric according to claim 8, wherein: The carbon material includes at least one of carbon black, graphene, graphene oxide, graphite, and carbon nanotubes; and / or, the surfactant comprises at least one of alkylbenzene sulfonate, alkyl sulfonate ester, alkyl sulfonate, alkyl sulfate, olefin sulfonate, and cycloalkaneate; and / or, the mass ratio of the carbon material to the surfactant is (0.8-1.2):1; And / or, the surface water contact angle of the modified fabric substrate is less than 90°, and the sheet resistance is less than 100Ω / sq; And / or, in the moisture power generation fabric, the area ratio of the coated area to the uncoated area is (1-9):3; And / or, in the moisture power generation textile, the coated area serves as a negative electrode, and the uncoated area serves as a positive electrode.
10. An application of moisture power generation fabric, characterized in that: The moisture power generation fabric according to any one of claims 1 to 6 or the moisture power generation fabric prepared by the method according to any one of claims 7 to 9 is applied to a moisture induced power generation device.
Citation Information
Cited By
Silk-screen printing textile-based wet power generation device and preparation method and application thereof
CN122026745A
Self-repairing fiber moisture power generation fabric as well as preparation method and application thereof
CN122039296A